Teaching creative and critical thinking an interactive workbook - Schiering, Marjorie S. 1943- (Lanham Rowman & Littlefield, 2016)
This workbook contains over sixty activities for learning-through-play. The activities were created by teacher-candidates, retired educators, and student-learners. They include interdisciplinary activities for first through twelfth grade levels. Each activity includes how-to-implement instructions along with applicable learning standards.--WorldCat.
Learning-through-play -- The IM and IBR with four interactive resources -- Creative cognition, critical thinking and metacognition -- The IM and IBR: summing up the method and strategy.
Includes bibliographical references (pages 197-200).
Keywords: Creative thinking -- Study and teaching; Creative teaching